Myanmar : Technical Assistance Report-Monetary Operations. (IMF Staff Country Reports; Country Report ;, 2019)
This Technical Assistance Report presents discussions focused on the financial market's developments and monetary operations-related issues. the data collected by the Central Bank of Myanmar (CBM) show that there already exist a significant number of uncollateralized interbank (I/B) transactions in Myanmar, but that the data on these transactions are not effectively used. Analysis shows that banks are conducting both types of uncollateralized transactions rather actively, while the total number and amount of the I/B deposit market are higher than those of the I/B borrowing market. It is recommended that efforts to correct data discrepancy should be continued and that this issue should be solved as soon as possible. It is necessary to find the data discrepancy in a timely manner, correct the data, and ask the reasons for misreporting by communicating with banks. In order to ensure the smooth preparation for the next fiscal year, a recommendation has been made to start preparing the liquidity forecasting for the next fiscal year as soon as possible.